Web-based Billing and Collection System for a Municipal Water and Services Unit - Pelandiana, A L; Ado, R G (KnE Social Sciences, 2018)
Web-Based Billing and Collection System for a Municipal Water and Services Unit is a system that sought to address the problem of a municipal water unit. Using the technology, meter reading will be paperless. It can be accessible through the Internet; end-users and water consumers/customers could connect and perform transactions enabling them to become efficient on their daily tasks whether in the office or at home. The head of the unit can make overall viewing of the status of daily transactions and can be viewed using desktop, laptop computers and android mobile devices connected to the internet. The water consumers/customers may receive email and short messaging system showing their current water consumption and water bill. Added/unique features such as graphical chart showing regular water consumptions on the end-users and consumers/customers dashboard as well as on their billing statements are provided. On the level of satisfaction of the respondents on the features of the proposed billing and collection system; result show that efficiency earned the highest weighted mean (4.43) interpreted as “satisfied”. Functionality posed weighted arithmetic mean (4.33) verbally interpreted as “satisfied”. Portability and reliability followed next. On the level of acceptance of the proposed billing and collection system; respondents’ acceptance according to consumer accounts updating gauged at 4.35 weighted arithmetic mean with verbal interpretation of “acceptable”. Auto-reminding the consumers for bills due for payment posed a 4.37 weighted arithmetic mean and was also “acceptable”. According to billing statement printing and free format report generation, respondents recorded 4.45 weighted arithmetic mean and interpreted as “acceptable”. Keywords: billing system, ewater, municipal water, web-based billing, collection system.